1990
DOI: 10.1161/01.atv.10.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Antisera and monoclonal antibodies specific for epitopes generated during oxidative modification of low density lipoprotein.

Abstract: Increasing evidence indicates that low density lipoprotein (LDL) has to be modified to Induce foam cell formation. One such modification, oxidation of LDL, generates a number of highly reactive short chain-length aldehydlc fragments of oxidized fatty acids capable of conjugating with lyslne residues of apoprotein B. By Immunizing animals with homologous malondlaldehyde-modlfled LDL (MDA-LDL), 4-hydroxynonenal-LDL (4-HNE-LDL), and Cu ++ -oxldlzed LDL, we developed polyvalent and monoclonal antibodies against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
379
1
10

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(400 citation statements)
references
References 38 publications
10
379
1
10
Order By: Relevance
“…The results of these studies were rather disappointing, because the results were often conflicting and failed to produce a clear cut indication of the clinical value of modified lipoprotein antibody assays as biomarkers for the development and/or progression of atherosclerosis. While some groups reported a positive correlation between the levels of oxLDL antibodies and different endpoints considered as evidence of atherosclerotic vascular disease, such as progression of carotid atherosclerosis or risk for the future development of myocardial infarction [21][22][23][24][25][26][27], others failed to show such correlation or showed an inverse correlation [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Modified Lipoprotein Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies were rather disappointing, because the results were often conflicting and failed to produce a clear cut indication of the clinical value of modified lipoprotein antibody assays as biomarkers for the development and/or progression of atherosclerosis. While some groups reported a positive correlation between the levels of oxLDL antibodies and different endpoints considered as evidence of atherosclerotic vascular disease, such as progression of carotid atherosclerosis or risk for the future development of myocardial infarction [21][22][23][24][25][26][27], others failed to show such correlation or showed an inverse correlation [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Modified Lipoprotein Antibodiesmentioning
confidence: 99%
“…The precise nature of the epitopes that elicit autoimmune responses has yet to be defined, but in vitro modified human LDL, e.g. copper oxidized, MDA modified, and AGE modified, are immunogenic in laboratory animals and are also recognized by spontaneously formed human autoantibodies [4][5][6][7]. Human autoantibodies reactive with oxLDL were the first to be purified and characterized [8][9][10] and human AGE-LDL antibodies have also been isolated and characterized [11].…”
Section: Introductionmentioning
confidence: 99%
“…51 We have recently shown that obese subjects have an increased skeletal muscle content of 4-Hydroxynonenal (4-HNE), a by-product of lipid peroxidation, 52 as compared with lean and ETr subjects. 9 The production of lipid peroxidation by-products, such as 4-Hydroxynonenal (4-HNE) and malondialdehyde (MDA), may reduce insulin sensitivity by increasing paracrine factors, such as TNFa.…”
Section: The Potential Pathways Linking Imtgs With Insulin Resistancementioning
confidence: 99%
“…The investigation of the possible pathogenic role of circulating oxLDL antibodies has produced conflicting data. While some groups reported a positive correlation between the levels of free oxLDL antibodies and different endpoints considered as evidence of atherosclerotic vascular disease, progression of carotid atherosclerosis, or risk for the future development of myocardial infarction, (13)(14)(15)(16)(17)(18)(19) others failed to show such correlation or showed an inverse correlation. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) On the other hand, there is a significant body of evidence supporting a pathogenic role for immune complexes formed by oxLDL and their corresponding antibodies (oxLDL IC), both in what concerns atherosclerosis and macrovascular disease (5;9;30-34) and nephropathy.…”
Section: Introductionmentioning
confidence: 99%